2020
DOI: 10.2471/blt.19.243998
|View full text |Cite
|
Sign up to set email alerts
|

Sales of anti-cancer medicines; China, Indonesia, Kazakhstan, Malaysia, Philippines and Thailand

Abstract: Objective To assess sales of anti-cancer medicines in the 2017 World Health Organization’s WHO Model list of essential medicines in China, Indonesia, Kazakhstan, Malaysia, Philippines and Thailand from 2007 (2008 for Kazakhstan and Malaysia) to 2017. Methods We extracted sales volume data for 39 anti-cancer medicines from the IQVIA database. We divided the total quantity sold by the reference defined daily dose to estimate the total number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…These results are similar to a published study that showed that sales from 2007 to 2017 across all types of anti-cancer therapies increased in China. 40 In contrast, our study showed that procurement of one third of the essential medicines decreased. At the provincial level, we also found that the procurement of essential medicines decreased in more than half the provinces, and the procurement of targeted medicines decreased only slightly in one province.…”
Section: Discussioncontrasting
confidence: 67%
“…These results are similar to a published study that showed that sales from 2007 to 2017 across all types of anti-cancer therapies increased in China. 40 In contrast, our study showed that procurement of one third of the essential medicines decreased. At the provincial level, we also found that the procurement of essential medicines decreased in more than half the provinces, and the procurement of targeted medicines decreased only slightly in one province.…”
Section: Discussioncontrasting
confidence: 67%
“…In recent years, the increase in the demand volumes for anticancer medicines is a common phenomenon across many countries. 19 The fast-growing utilization of anticancer medicines is a positive performance for cancer patients in China, which means that the availability of these medicines is increasing. There are several main factors associated with changes in utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Of concern are potential barriers to access to and affordability of essential cancer drugs recommended in the WHO EML. [29][30][31][32][33][34][35] Arguably, access and affordability are only relevant considerations for WHO EML cancer drugs with established clinical benefit, and most importantly, OS benefit. In recent years, the WHO has put greater emphasis on the development and use of explicit clinical benefit criteria to inform the selection of cancer drugs for the EML.…”
Section: Discussionmentioning
confidence: 99%